2020
DOI: 10.1109/access.2019.2948263
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Useful Life Prediction With Fusing Failure Time Data and Field Degradation Data With Random Effects

Abstract: Accurate remaining useful life (RUL) prediction has a great significance to improve the reliability and safety for key equipment. However, it often occur imperfect or even no prior degradation information in practical application for the existing RUL prediction methods, which could produce prediction error. To solve this issue, this paper proposes a two-step RUL prediction method based on Wiener processes with reasonably fusing the failure time data and field degradation data. First, we obtain some interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…By substituting the (33)- (35) into k L , we can obtain the profile likelihood function about  , as shown in (36).…”
Section: A Online Updating the Random Parameter Based On The Joint Ementioning
confidence: 99%
See 4 more Smart Citations
“…By substituting the (33)- (35) into k L , we can obtain the profile likelihood function about  , as shown in (36).…”
Section: A Online Updating the Random Parameter Based On The Joint Ementioning
confidence: 99%
“…As the field degradation data increases, the credibility of the field degradation information becomes higher. Therefore, the number of iterations of parameters updating can be selected based on the credibility of the prior information and the number of field degradation data, which reflects the credibility of the field degradation data [35]. In the later simulation experiments, it is found that the converged results of the EM algorithm are a certain distance away from the MLE, which may be caused by the "Fminsearch" search function in Matlab.…”
Section: Parameter Updating Based On a Heuristic Algorithmmentioning
confidence: 99%
See 3 more Smart Citations